Analysis of Microplastic Abundance on the Coast of South Lampung as a First Step in Pollution Control - Marlina Kamelia; Aulia Ulmillah; Pawhestri, Suci Wulan (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
Microplastics pose serious threats as they can  contaminate various ecosystems, ranging from seawater surfaces, beach sands, freshwater sediments, coastal sediments, to deep-sea environments. Their presence, particularly in coastal areas, exerts significant negative impacts on ecosystem balance and human health. This study aimed to analyze the types and abundance of microplastics in seawater and sediments of South Lampung’s coastal area, measure related environmental parameters (BOD, COD, pH, temperature, and current velocity), and provide baseline data to support strategies for pollution control. The research was conducted using an experimental method at six stations located 50–100 meters apart. Water and sediment samples were collected, filtered, separated, and analyzed using Fourier Transform Infrared Spectroscopy (FTIR) to identify polymer types. The results revealed that microplastics were detected at all stations, with dominant polymers including polyethylene (PE), polypropylene (PP), polyester (PES), polystyrene (PS), and smaller amounts of polyamide. Physico-chemical parameters of the waters were generally within acceptable thresholds, although BOD levels at several stations slightly exceeded the quality standards, indicating a relatively high organic load. This study confirms that microplastic pollution has already occurred in the South Lampung coastal area, dominated by polymers originating mainly from anthropogenic activities such as household waste, synthetic textiles, and coastal activities. As such, this research provides an essential initial step in mapping microplastic pollution in the region.